Enhanced levels of IL-6 and PAI-1 and decreased levels of MMP-3 in cytomegalovirus seropositive patients with prior myocardial infarction - Xinling Xu; Angela Silveira; Pia Lundman; Afsar Rahbar; Cecilia Söderberg-Nauclér (International Journal of Cardiology: Heart & Vasculature)
Background: Efforts to understand atherosclerosis, a major cause of ischemic heart disease, have linked several lifestyle factors to increased risk for developing cardiovascular disease. Some studies suggest that cytomegalovirus (CMV), a widely prevalent herpesvirus, is reactivated in atherosclerotic plaques and associated with higher cardiovascular mortality risk. We aimed to explore whether CMV seropositivity and CMV-IgG antibody levels correlate with relevant biomarkers in a cohort of patients with myocardial infarction (MI) and matched controls. Methods and results: We analyzed a dataset from 324 survivors of MI treated in Stockholm between 1996 and 2001. Blood samples collected three months after MI were used to measure protective Apo B100 autoantibodies, metabolic, and inflammatory biomarkers. CMV serology was performed on stored serum samples. Correlation analyses were conducted between biomarkers and CMV serostatus in 324 patients and age- and sex-matched controls. While CMV seroprevalence was equal, the CMV-IgG levels were higher in controls. Among various factors examined, CMV seropositive MI patients had elevated levels of plasminogen activator inhibitor-1 (PAI-1) and interleukin-6, along with lower levels of MMP-3, than CMV seronegative MI patients. CMV-IgG levels correlated positively with PAI-1 levels in patients. Although CMV seropositivity was associated with increased proinsulin levels, there was no correlation with diabetes diagnosis. Conclusions: Our findings suggest an enhanced inflammatory and prothrombotic state in CMV seropositive patients after MI. Notably, patients had lower levels of CMV IgG than controls.